EVALUASI SISTEM E-LEARNING BIDANG PENDIDIKAN KEDOKTERAN PADA PROGRAM ONLINE COURSE AIPKI WILAYAH IV - Tri Suwarno; Diani Puspa Wijaya (EDUTECH, 2023)
Faculty of Medicine (FM UII) is part of the Association of Indonesian Medical Education Institutions (AIPKI) Region IV. FM UII through the online course program opens elective block courses by implementing an e-learning system. The aim of this research is to investigate the factors that influence the adoption of e-learning in medical education elective programs. The method used in this study uses the Human, Organization and Technology-Fit (HOT-Fit) framework where the aspects studied include aspects of users, organizations, and technology to provide more benefits in implementing e-learning. Data analysis was performed by regression. A total of 124 respondents were used in this study. Hypothesis testing showed that there were 11 accepted hypotheses and 6 rejected hypotheses. From this study it can be concluded that the implementation of the e-learning system in general has provided benefits to its users. But on the other hand, the implementation of e-learning still needs to be improved to be able to achieve more benefits for students by paying attention to aspects of user satisfaction (human), adequate organizational and technological support. This research can provide recommendations for models of implementing online learning that are in accordance with the characteristics of institutions, especially in medical education in Indonesia.